Validation of the Greek Version of the Fibromyalgia Rapid Screening Tool. Issue 7 (22nd February 2017) - Zis, Panagiotis; Brozou, Vassiliki; Stavropoulou, Evmorfia; Argyra, Erifilli; Siafaka, Ioanna; Kararizou, Evangelia; Bouhassira, Didier; Perrot, Serge; Zis, Vassileios; Vadalouca, Athina
Abstract: Background and Aim: The Fibromyalgia Rapid Screening Tool (FiRST) is a brief, simple, and straightforward self‐administered questionnaire that was developed by Perrot et al. for the detection of fibromyalgia syndrome in patients with diffuse chronic pain. The aim of our study was to develop and validate the Greek version of FiRST. Methods: The study was set up as a prospective observational study. The original French version of FiRST was adapted into Greek using forward and backward translation. Patients with chronic diffuse pain with a clinical diagnosis of fibromyalgia and osteoarthritis based on the criteria of the American College of Rheumatology were invited to participate to the study. Results: Of the 101 patients who met our inclusion criteria, 42 were diagnosed with fibromyalgia and 59 with osteoarthritis. The 2 groups did not differ significantly regarding gender and pain characteristics (duration, intensity). Cronbach's alpha coefficient was 0.79. Receiver operating characteristic analysis showed an area under the curve of 89% (95% confidence interval = 83 to 95%; SE: 0.032, P  <   0.001). At a cutoff score of ≥ 5, FiRST showed a sensitivity of 86%, a specificity of 83%, a positive predictive value of 78%, and a negative predictive value of 89%. The intraclass coefficient for the test–retest reliability was 0.96. Conclusion: The Greek version of FiRST is a valid screening tool for fibromyalgia in daily practice.